Analysis of ultra-heavy plate rolling force based on thickness temperature gradient elements and experiment simulations. (February 2017) - Wang, HY; Ding, JG; Lu, X; Zhang, DH; Zhao, DW
The thickness of the plate in temperature gradient rolling is first divided into 2 m elements, and m is an undetermined parameter which can be limited. Based on these thickness elements with different temperatures, the rolling force of this advanced process is first analyzed with slab method. Also the predictions of thickness ratio with different temperatures and reductions of each thickness elements are proposed in this paper. The results measured after rolling experiments are used to compare with these calculated by this model in order to verify its accuracy. In the experiment, a multi-metals riveting plate in the same temperature is designed to simulate a single metal one in gradient temperatures based on the thickness elements. Since the model is based on an analytical method which is strongly supported by the rolling theories, it can be applied in real gradient temperature rolling for ultra-heavy plate.